2020
DOI: 10.1002/gch2.201900076
|View full text |Cite
|
Sign up to set email alerts
|

MOF@PEDOT Composite Films for Impedimetric Pesticide Sensors

Abstract: Due to its deleterious effects on health, development of new methods for detection and removal of pesticide residues in primary and derived agricultural products is a research topic of great importance. Among them, imazalil (IMZ) is a widely used post‐harvest fungicide with good performances in general, and is particularly applied to prevent green mold in citrus fruits. In this work, a composite film for the impedimetric sensing of IMZ built from metal‐organic framework nanocrystallites homogeneously distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…[ 122–125 ] Hence, designing MOF composites together with desired conductive polymers or carbon is promising to construct ideal cathode frameworks and deliver a large discharge capacity. [ 126,127 ] Notably, the Cui group concluded that the conductivity of the common conductive polymers, [ 128 ] like polyaniline (denote PANI), polypyrrole (denote PPY), and poly(3,4‐ethylenedioxythiophene) (denote PEDOT), increased as follows: PANI < PPY < PEDOT, suggesting that the PEDOT possess the best conductivity. Therefore, exploiting potential MOF composites with PEDOT could lead to high conductivity, thus promoting low internal resistance and fast electron migration.…”
Section: Enhancing the Conductivity Of Mof‐derived Nanostructuresmentioning
confidence: 99%
“…[ 122–125 ] Hence, designing MOF composites together with desired conductive polymers or carbon is promising to construct ideal cathode frameworks and deliver a large discharge capacity. [ 126,127 ] Notably, the Cui group concluded that the conductivity of the common conductive polymers, [ 128 ] like polyaniline (denote PANI), polypyrrole (denote PPY), and poly(3,4‐ethylenedioxythiophene) (denote PEDOT), increased as follows: PANI < PPY < PEDOT, suggesting that the PEDOT possess the best conductivity. Therefore, exploiting potential MOF composites with PEDOT could lead to high conductivity, thus promoting low internal resistance and fast electron migration.…”
Section: Enhancing the Conductivity Of Mof‐derived Nanostructuresmentioning
confidence: 99%
“…MOFs have shown potential as good detection materials for pesticides. [ 215 ] The pores and multifunctional sites of MOFs readily bind with organic and inorganic functionalities in the pesticides. The presence of amino, halogen, nitro, phosphorus, or sulfur functionalities in pesticide molecules facilitates binding with MOF metal centers and ligand functional sites through noncovalent interactions.…”
Section: Mofs Sensing Behavior Toward Toxic Chemicalsmentioning
confidence: 99%
“…They employed the probe for the detection of pesticide imazalil (IMZ). [107] Bimetallic or multimetallic MOFs have a greater advantage due to their simple syntheses, low cost and less energy consumption. Song et al made use of mixed organic linkers for developing a CoÀ Ni bimetallic MOF (CoNi-MOF).…”
Section: Impedimetric Sensormentioning
confidence: 99%
“…They studied the conducting properties of the film upon the addition of different solutions. They employed the probe for the detection of pesticide imazalil (IMZ) [107] . Bimetallic or multimetallic MOFs have a greater advantage due to their simple syntheses, low cost and less energy consumption.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%